Implementation of formal institutions in the studies of Kyiv Economic School of the 19th century - Yu.V. Ushchapovskyi (Економіка, управління та адміністрування)
The paper carries out the retrospective analysis of modern institutionalism of formal institutions and institutional order in the works of Kyiv Economic School representatives of the 19th century: Mykola Bunge, Afinogen Antonovich and Dmytro Pikhno. Particular attention is paid to the study of the problem of implementation of new institutions and its connection with the interests of society, the importance of the state in creating institutional constraints and shaping the institutional order. Bunge’s M. understanding of the economic order in the field of modern institutional analysis is investigated. The article analyzes the influence of the scientist on the economic policy of the Russian Empire as the Minister of Finance in the context of the problem of implementation of the institution of industrial freedom, which aims to unlock the creative potential of society. Antonovich’s A. understanding of the role and place of the state in creating a favorable institutional environment as an external element for economic development is clarified. Pikhno’s D. understanding of the problem of the depth of state intervention in economic life and the view of economic laws as a specific limiting factor of such intervention are emphasized. The author concludes that the representatives of the Kyiv School of Economics were examining the institutional order in the context of the economic activity of the state. In particular, M.Bunge emphasized the importance of institutional constraints and the formation of institutional order in the context of the combination of individual and public interests; A.Antonovich put the problem of the implementation of institutions directly dependent on the people's awareness of their freedom, their intellectual and moral development; D.Pikhno understood economic laws as the limiting factor in the depth of state intervention in economic processes.